Frankie - Sullivan, Mary, 1958- (Boston : Houghton Mifflin Harcourt, 2017)
When shelter dog Frankie arrives at his new home, he finds that all of the toys belong to the other dog in the house, Nico, but they soon find a way to share.
Preschool
Keywords: Dogs -- Juvenile fiction; Sharing -- Juvenile fiction; Dogs -- Fiction; Sharing -- Fiction; Sharing -- Juvenile fiction; Sharing -- Fiction; Dogs -- Juvenile fiction; Dogs -- Fiction